Gender differences in caregiver burden and its determinants in family members of terminally ill cancer patients. Issue 7 (18th October 2015) - Schrank, Beate; Ebert‐Vogel, Alexandra; Amering, Michaela; Masel, Eva K.; Neubauer, Marie; Watzke, Herbert; Zehetmayer, Sonja; Schur, Sophie
Abstract: Objective: Female family caregivers consistently report higher levels of stress and burden compared to male caregivers. Explanations for the apparently higher psychological vulnerability of female caregivers are largely missing to date. This study assesses the correlates and determinants of caregiver burden in family caregivers of advanced cancer patients with a specific focus on gender differences. Methods: Three hundred and eight self‐identified main informal caregivers of advanced cancer patients were cross‐sectionally assessed using structured questionnaires for caregiver burden and hypothesised determinants of burden, including sociodemographic characteristics, caring arrangements, support needs, hope and coping style. Gender differences and predictors of burden were assessed using t ‐tests, chi‐squared tests and univariate linear regression. Significant univariate predictors were entered in an analysis of covariance separately for men and women. Results: Burden was significantly higher in women. Hope was the most significant protective factor against burden in both genders, together with perceived fulfilment of support needs. Only in women emotion‐oriented coping and being in employment while caring were significantly predictive of higher burden in the multivariate analysis. The model explained 36% of the variance in burden in men and 29% in women. Conclusion: Psychological support interventions for family caregivers should take gender‐specific risk factors into account. Interventions focusing on keeping up hope while caring for a terminally ill family member may be a valuable addition to palliative services to improve support for family carers. Women may benefit from interventions that address adaptive coping and strategies to deal with the dual demands of employment and caring. Copyright © 2015 John Wiley & Sons, Ltd. Copyright © 2015 John Wiley & Sons, Ltd.